Harnessing oil refinery exhaust heat via organic rankine cycle for green hydrogen production toward net-zero emissions - Hajianto, Muhamad Roni; Mutaqien, Gilang Nurul; Wibowo, Dipta Ario; Latifin, Latifin (Jurnal Polimesin, 2025)
The increasing CO2 emissions and the complexity of human activities have driven the Indonesian government to enact Law Number 16 of 2016 to achieve greenhouse gas emission reduction targets by 2030. Oil refineries, which previously only disposed of waste heat without being utilized, have now become potential sources of sustainable energy. Through the development of Organic Rankine Cycle (ORC) technology, this waste heat can be converted into electricity. This research focuses on four types of working fluids, namely Propane, Isopentane, Isobutane, and R245fa. The results showed that the electricity generated from each ORC system was 18.34 MWh (Propane), 52.77 MWh (Isopentane), 32.17 MWh (Isobutane), and 21.23 MWh (R245fa), respectively. This electricity can be used to produce green hydrogen through electrolysis methods, resulting in 366.83 kg (Propane), 1055.42 kg (Isopentane), 643.33 kg (Isobutane), and 424.67 kg (R245fa) of green hydrogen. Compared to hydrogen production through fuel technology, ORC implementation can reduce CO2 emissions by 12.64 t.CO2 (Propane), 36.36 t.CO2 (Isopentane), 22.16 t.CO2 (Isobutane), and 14.63 t.CO2 (R245fa). All calculations were based on 24-hour operation. Isopentane produces the highest power among the four other organic working fluids and generates the largest profit from green hydrogen production through electrolysis processes, amounting to Rp. 55,069,944.78 per day. The innovation of applying ORC systems in oil refineries is an effective step in reducing carbon emissions to support sustainable energy production.